Comparative Analysis of COL9A1 Genotyping in Oral Squamous Cell Carcinoma Diagnosis: A Pilot Study - Alexandra Roi; Nicoleta Ioana Andreescu; Ciprian Ioan Roi; Meda-Lavinia Negruțiu; Cosmin Sinescu; Mircea Riviș; Madalina Veronica Boruga; Laura-Cristina Rusu (Applied Sciences, 2021)
The epidemiology of OSCC continues to increase despite the progress that has been made. More than ever, the diagnostic approach process needs to focus on genetic and epigenetic alterations. The aim of our study was to identify and correlate the presence of COL9A1 gene variants in two types of samples from OSCC patients. Methods: Our pilot study included 32 subjects diagnosed with OSCC. Fresh tumour tissue and peripheral blood samples were used in order to identify the genotypes of the COL9A1 gene. Variables, such as age, gender and tobacco and alcohol use, were also taken into consideration. The DNA analysis of the samples was based on a tagged SNP (rs550675) for the allelic discrimination. Results: The statistical significance and correlation of the COL9A1 genotypes within the two categories of samples was statistically significant (p < 0.001) for the C/T and T/T genotypes, providing an important perspective on the potential identification in blood samples of the gene mutation encountered in OSCC. Conclusions: This is the first study that focused on providing preliminary results using blood samples via the identification of COL9A1 gene variants in OSCC patients. The possibility of introducing a liquid biomarker by targeting this genetic variant is an appealing perspective for screening and diagnosis.